Communication Strategy of The Office of Women's Empowerment Child Protection Population Control and Family Planning (DP3AP2KB) in Handling Cases Stunting in the Banda Aceh City Region, Aceh Province, Indonesia - MA, Mahfudh; Zulkarnain, Iskandar; Mazdalifah (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to analyze the communication strategies used by the Women's Empowerment, Child Protection, Population Control, and Family Planning Service (DP3AP2KB) in handling stunting cases in the Banda Aceh City area. The theories and concepts used in this research are communication strategies related to planning and implementation starting from strategic steps as put forward by Anwar Arifin. The research method used in this research is a qualitative research method with a descriptive approach. Researchers used Miles Huberman and Saldana's data analysis method which includes data condensation (data condensation), data presentation (data display), and then draw conclusions(conclusion). The results of this research show that DP3AP2KB implements a communication strategy through a collaborative communication approach, using various methods and communication channels, collaborative communication includes government communication, interpersonal communication, development communication, and family communication.